Application of Averrhoa Blimbi, L and Activated Carbon to Measure the Characteristics of No-Load Output Voltage, Output Voltage with LED Load and LED Voltage Drop - Adi Mulyadi; Muhammad Zainal Roisul Amin; Susilo; ST Fatimah (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2025)
This paper discusses the use of Averrhoa bilimbi L. (blimbing wuluh) liquid and powdered activated carbon to examine the output voltage characteristics and voltage drop in LEDs. Previous studies using various fruits and fermentation methods showed inconsistent output voltages, prompting the use of Averrhoa bilimbi due to its natural citric acid content, which can produce a small but measurable voltage (0–499 mV). To improve this voltage, activated carbon (MES size 70329-06950) was added to the mixture. The experimental setup included Zn and Cu electrodes, a 30V 5A power supply, and liquid volumes of 75 ml, 100 ml, and 125 ml tested over durations of 1, 5, and 10 minutes. Results showed that without activated carbon, the output voltage ranged from 350–499 mV, while LED voltage dropped slightly (8–0 mV). With activated carbon, output voltage significantly increased to 434–660 mV, while the LED voltage remained stable and the drop minimal. These findings indicate that the addition of activated carbon enhances the electrical output of Averrhoa bilimbi and reduces voltage loss, suggesting its potential use as a simple, renewable bioenergy source for low-power applications.